Reconstruction of Corporate Criminal Liability for Corruption Crimes in the Banking Sector Based on Justice and Legal Certainty - Indra Gunawan Purba (Britain International for Academic Research (BIAR-Publisher), 2026)
Corruption in the banking sector constitutes one form of corporate crime that has broad implications for the stability of the financial system, public trust, and the national economy. Such conditions create legal uncertainty and potentially hinder the realization of substantive justice in the eradication of banking corruption. This study aims to analyze the legal framework governing corporate criminal liability for banking corruption in Indonesia, identify normative and practical weaknesses that have caused corporate punishment to remain suboptimal, and formulate a reconstructed model of corporate criminal liability based on justice and legal certainty. This research employs a normative legal research method using statutory, conceptual, and case approaches. Primary legal materials consist of legislation, court decisions, and related legal documents, which are analyzed qualitatively by applying theories of corporate criminal liability, justice, and legal certainty. The findings reveal that the regulation of corporate criminal liability in banking corruption cases remains sectoral and has not yet provided clear parameters regarding the attribution of corporate fault, identification of controlling actors, and the relationship between individual fault and corporate fault. There are inconsistencies in judicial practice that often allow corporations to evade criminal sanctions despite having benefited from corruption committed by their directors or employees. Therefore, a reconstruction of the corporate criminal liability system is required through the affirmation of a corporate fault model integrating the doctrines of identification theory, aggregation theory, and the corporate culture model, accompanied by clearer regulations concerning the criteria of corporate fault, evidentiary mechanisms, and proportional and effective sanctions. This study concludes that the reconstruction of corporate criminal liability for banking corruption must be directed toward establishing a legal system capable of balancing the values of justice, legal certainty, and utility through the explicit recognition of corporations as independent criminal offenders, thereby enabling the eradication of corruption in the banking sector to be carried out more effectively, consistently, and fairly.